Hospital-based sentinel surveillance for bacterial meningitis in under-five children prior to the introduction of the PCV13 in India. Issue 28 (23rd June 2021) - Jayaraman, Yuvaraj; Veeraraghavan, Balaji; Girish Kumar, C.P.; Sukumar, Bharathy; Rajkumar, Prabu; Kangusamy, Boopathi; Verghese, Valsan Philip; Varghese, Rosemol; Jayaraman, Ranjith; Kapoor, Ambujam Nair; Gupta, Nivedita; Kanagasabai, K.; et al.
Highlights: Generated data on bacterial meningitis burden among under-five children in India. S. pneumoniae the commonest etiology with high proportion of MDR strains. Two-thirds of pneumococcal serotypes covered by PCV13. Continued surveillance needed to assess the impact of PCV following introduction. Abstract: Introduction: A hospital-based sentinel surveillance network for bacterial meningitis was established in India to estimate the burden of bacterial meningitis, and the proportion of major vaccine-preventable causative organisms. This report summarises the findings of the surveillance conducted between March 2012, and September 2016 in eleven hospitals. Methods: We enrolled eligible children with bacterial meningitis in the age group of one to 59 months. CSF samples were collected and processed for biochemistry, culture, latex agglutination, and real-time PCR. Pneumococcal isolates were serotyped and tested for antimicrobial susceptibility. Results: Among 12 941 enrolled suspected meningitis cases, 586 (4.5%) were laboratory confirmed. S. pneumoniae (74.2%) was the most commonly detected pathogen, followed by H. influenzae (22.2%), and N. meningitidis (3.6%). Overall 58.1% of confirmed bacterial meningitis cases were children aged between one, and 11 months. H. influenzae meningitis cases had a high (12.3%) case fatality rate. The serotypes covered in PCV13 caused 72% pneumococcal infections, and the most common serotypes were 14 (18.3%), 6B (12.7%) and 19F (9.9%). Non-susceptibility to penicillin was 57%. Forty-five (43.7%) isolates exhibited multidrug resistance, of which 37 were PCV13 serotype isolates. Conclusions: The results are representative of the burden of bacterial meningitis among under-five children in India. The findings were useful in rolling out PCV in the National Immunization Program. The non-susceptibility to penicillin and multidrug resistance was an important observation. Timely expansion of PCV across India will significantly reduce the burden of antimicrobial resistance. Continued surveillance is needed to understand the trend after PCV expansion in India.